Case Management and Health-Related Quality of Life Outcomes in a National Sample of Persons with HIV/AIDS - Cunningham, William E. (2008)
OBJECTIVE: To examine whether having a case manager is associated with better physical and mental health scores (PH and MH). BACKGROUND: HIV/AIDS is a condition characterized by a variety of medical and social needs that vary between individuals and over time. Case-management has been advocated as a means to improve problems of access, cost and outcomes of HIV/AIDS care. METHODS: We analyzed data from a nationally representative sample of 2251 HIV positive persons receiving care in the in the HIV Costs and Services Utilization Study (HCSUS). Participants were interviewed at baseline and approximately 18 months later. Data were collected on use of case-management, sociodemographics, antiretroviral therapy, and health-related quality of life (HRQOL). We examined bivariate and multivariate associations of case-management at baseline with change in PH and MH at follow-up. RESULTS: We found that having contact with a case-manager at baseline significantly predicted improvement in PH (regression coefficient = 1.02, p < 0.05) among those not receiving HAART. We found no association of case management with MH among those not receiving HAART and those receiving HAART in multivariate analysis. CONCLUSIONS: Our findings support a beneficial relationship between case managers and physical health for patients with HIV but only among those not already receiving recommended treatment with HAART.